Character Segmentation on Degraded Printed ODIA Script - Pattnaik, Ipsita; Patnaik, Tushar (International Journal of Computer Sciences and Engineering, 2020)
In this paper segmentation procedure of degraded script have been proposed of Odia script. A dataset of 50 documents including 170 words in each document making of 5000 character have been taken after scanning. After that segmentation procedure have been applied to get the accuracy rate of degraded printed Odia script. Also, different level of degradation in a script have been mentioned. Character segmentation on degraded odia printed script have been a tough task due to its Curvy with round format. Due to this style of writing it becomes difficult to segment its Characters. Character Segmentation is an essential part of Optical Character Recognition. Optical Character Recognition is an emerging area of research which helps in converting scanned image or handwritten notes into digital format.